Membuat Bencana Jadi Tren: Studi pada #KalselJugaIndonesia di Twitter (Jurnal Kajian Media, 2023)
Often referred to as a world disaster laboratory, Indonesia is one of the most prone to natural disasters globally. Disasters can happen at any time. Good disaster management is necessary given the colossal impact of disasters. Disaster communication is also vital in disaster management and is now closely related to social media. In a disaster situation, three types of information are commonly circulated on social media, namely situational information, sentiments, and personal opinions. This study attempts to map out the dominant information in the hashtag #KalselJugaIndonesia, which is related to the flood disaster in South Kalimantan last January 2021, which managed to become a trending topic overcoming other disaster discourses at the same time. This research is descriptive qualitative research with a directed qualitative content analysis method. As a result, it was found that sentiments of sympathy, sadness, and anger were the main drivers of the hashtag #KalselJugaIndonesia. In addition, the inclusion of this unusual and discourse-filled hashtag is the reason why people's attention can be drawn to the flood disaster in South Kalimantan at that time.